Hubungan Praktik Pengasuhan dan Perilaku Eliminasi, Terapan Model Promosi Kesehatan (HPM) pada Anak Prasekolah di JABODETABEK: Studi Cross-Sectional - Eka Rokhmiati Wahyu Purnamasari; Desy Sulistiyorini (UIMA Press, 2023)
Background: The practice of parenting for preschool age children is not yet in demand by parents. The application of the health promotion model (HPM) is a commitment to changing elimination behavior in the process of urinating and defecating. Objectives: The objective of this study was to determine behavior health promotion model (HPM) is associated with toilet training in preschool children. Methods: Desain cross-sectional quantitative study used 70 respondents in the areas of Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK). Using a Google Form questionnaire from September 12 -17 September 2022 distributed online. Result: Of the 70 participants, There was no parenting practice, and the elimination behavior of preschool age children was low, 39 (75.5%). Practice parenting has been done already, and the elimination behavior of preschool, high 13 (72.2%). There was a relationship between practice parenting and elimination behavior using the applied health promotion model (HPM) in preschool children, P-value of 0.001. Participation in parenting practice was 7.8 more effective against high elimination behavior in preschool age children. Conclusion: Parenting practice activity supported the success of preschool children's elimination behavior. Implementation of the health promotion model (HPM) in stages according to the child's growth and development.